Sacred Rhythm and Sunset Views: Elevating Uluwatu's Kecak Dance as a Cultural Tourism Icon - Jayanti Wardana, Pande Luh Putu Maharani; Aryasih, Putu Ayu; Santi Diwyarthi, Ni Desak Made; Darmiati, Made (Westscience Press, 2025)
This research explores strategic approaches to optimizing the management of the Half Day Sunset Over Uluwatu and Kecak Dance tour package at PT Destination Asia, aiming to boost tourist satisfaction—particularly by highlighting the artistic significance of the Kecak dance. A qualitative methodology was adopted, incorporating POAC (Planning, Organizing, Actuating, Controlling) and SWOT analysis frameworks. Data were collected through interviews, field observations, and questionnaires distributed to tourists who took part in the tour. The results emphasize that successful tour operations depend on meticulous planning, including the appropriate selection of tour guides, effective destination communication, and streamlined logistics. The SWOT analysis identified core strengths in cultural components, especially the Kecak dance, a distinctive Balinese performance rooted in Hindu epics, known for its hypnotic chanting and dynamic choreography. However, some challenges persist, such as discomfort for the audience during the show and technical inefficiencies in ticketing and crowd control. As the emotional and artistic centerpiece of the tour, the Kecak dance provides not only entertainment but also a deep cultural experience. To further enrich this experience, improvements in storytelling, stage aesthetics, and audience interaction are recommended. By implementing POAC strategies and drawing on insights from the SWOT analysis, PT Destination Asia can enhance its tour service quality, resolve current limitations, and deliver a more engaging and culturally enriching experience for visitors.